Downregulation of SOX2-OT Prevents Hepatocellular Carcinoma Progression Through miR-143-3p/MSI2 - Zhao, Hongfeng; Bi, Minping; Lou, Meng; Yang, Xiaowei; Sun, Liwen (Frontiers in Oncology, 2021)
Objective LncRNA SOX2-OT is involved in a variety of cancers. This study explored the effect of lncRNA SOX2-OT on hepatocellular carcinoma (HCC) cells. Methods SOX2-OT expressions were detected in HCC tissues and normal tissues, normal cells, and HCC cells. The relationship between SOX2-OT and prognosis was analyzed by TCGA. After SOX2-OT expression was inhibited using siRNA, HCC cell malignant behaviors were evaluated. The subcellular localization of SOX2-OT in HCC cells was predicted and analyzed. The binding relationships among SOX2-OT, miR-143-3p, and MSI2 were analyzed by bioinformatics website, dual-luciferase assay, and RNA pull-down assay. The effect of miR-143-3p and MSI2 on the regulation of SOX2-OT on biological behaviors of HCC cells was confirmed by functional rescue experiments. The effect of SOX2-OT on the tumorigenicity of HCC was evaluated by subcutaneous tumorigenesis in nude mice. Results SOX2-OT was highly expressed in HCC cells and tissues. The prognosis was poor in HCC patients with high SOX2-OT expression. Downregulating SOX2-OT inhibited HCC cell malignant behaviors. SOX2-OT bound to miR-143-3p to promote MSI2 expression. Downregulating miR-143-3p or upregulating MSI2 averted the role of si-SOX2-OT in HCC cells. Nude mouse subcutaneous tumorigenesis showed that SOX2-OT downregulation decreased the tumorigenicity of HCC, and affected the levels of miR-143-3p and MSI2 mRNA in tumor tissues. Conclusion SOX2-OT inhibited the targeted inhibition of miR-143-3p on MSI2 through competitively binding to miR-143-3p, thus promoting MSI2 expression and proliferation, invasion, and migration of HCC cells.